Welcome, caller, this is Chloe - Coriell, Shelley (Amulet Books, 2012)
Big-hearted Chloe Camden is the queen of her universe until her best friend shreds her reputation and her school counselor axes her junior independent study project. Chloe is forced to take on a meaningful project in order to pass, and so she joins her school’s struggling radio station, where the other students don’t find her too queenly. Ostracized by her former BFs and struggling with her beloved Gram’s mental deterioration, lonely Chloe ends up holding a call-in show that gets the station much-needed publicity and, in the end, trouble. She also befriends radio techie and loner Duncan Moore, a quiet soul with a romantic heart. On and off the air, Chloe faces her loneliness and helps others find the joy and fun in everyday life. Readers will fall in love with Chloe as she falls in love with the radio station and the misfits who call it home